Fiscal Crises - Gerling, Kerstin (IMF Working Papers; Working Paper ;, 2017)
A key objective of fiscal policy is to maintain the sustainability of public finances and avoid crises. Remarkably, there is very limited analysis on fiscal crises. This paper presents a new database of fiscal crises covering different country groups, including low-income developing countries (LIDCs) that have been mostly ignored in the past. Countries faced on average two crises since 1970, with the highest frequency in LIDCs and lowest in advanced economies. The data sheds some light on policies and economic dynamics around crises. LIDCs, which are usually seen as more vulnerable to shocks, appear to suffer the least in crisis periods. Surprisingly, advanced economies face greater turbulence (growth declines sharply in the first two years of the crisis), with half of them experiencing economic contractions. Fiscal policy is usually procyclical as countries curtail expenditure growth when economic activity weakens. We also find that the decline in economic growth is magnified if accompanied by a financial crisis.